Theology and Nursing Students' Knowledge of Organ Donation and Transplantation - Soylar, P.; Kadioglu, B. Ulan (Elsevier Science Inc, 2018)
Introduction. The aim of the present study was to evaluate the knowledge level of nursing and theology students, who will deliver health care and religious services in the future, about organ donation. Methods. This cross-sectional study was conducted with 578 university students at Firat University Faculty of Health Science Nursing Department and Faculty of Theology. Results. Of the participants, 49.3% were nursing students and 50.7% were theology students. Although 3.8% of the students stated that a family member had donated an organ, only 0.5% of all students had a donation card. Among the nursing students, 34.4% stated that they had no reason for not having a donation card and that they might donate in the future. Among the theology students, the rate was 27.3%. In terms of reasons for wishing to be an organ donor, religious beliefs were more important to theology students than to nursing students (18.4% and 16.1%, respectively). The nursing students' total score on the Organ-Tissue Donation and Transplantation Knowledge Scale was significantly higher than that of the theology students (P < .05). Conclusions. Although the current level of knowledge of nursing and theology students about organ donation and transplantation was adequate, the rate of organ donation was low. Therefore, not only health care professionals, but also religious officials have important roles to play in increasing the organ donation rate. Removing existing barriers to organ donation is important to resolve the current organ donation shortage in Turkey.
Keywords: Public-Attitudes; Health-Workers; University; Behavior; Religion; Faculty